Atomic and electronic properties of 2D Chevrel phases: A case study of the superatomic two-dimensional semiconductor Re6Se8Cl2 - Andrey N. Chibisov; Daria M. Smotrova; Mary A. Chibisova; Aleksandr S. Fedorov (Modern Electronic Materials)
The design of two-dimensional superatomic materials, which form their atomic structures through covalently bonded clusters with variable chemical compositions, will enable the development of new materials with promised electronic properties that are beneficial for modern nanoelectronics. This paper presents ab initio calculations of the atomic and electronic structures of both bulk and 2D Re6Se8Cl2. The calculations were carried out using density functional theory, incorporating noncollinear spin density and the pseudopotential method. The results include data on the atomic structure, band gap value, formation energy of the Re6Se8Cl2 2D layer, and the redistribution of atomic charges within the structures. The differences in effective masses for electrons and holes in the two-dimensional and bulk Re6Se8Cl2 materials are demonstrated, along with an explanation of how these differences impact their transport properties. The findings are expected to be of great significance for the design, synthesis, and implementation of new two-dimensional superatomic materials with controlled properties in modern nanoelectronics.